Becoming warriors: dramatic inquiry with 11- to 12-year-olds in an EBD classroom. Issue 1 (2nd January 2017) - Edmiston, Brian; Sobjack, Laura
ABSTRACT: Using a dialogue format, a college professor and a teacher of 11- to 12-year-old children with emotional and behavioural difficulties (EBD) report on a case study of four children (three boys and a girl) when over a three-week period dramatic inquiry pedagogy (focused on the meaning for students of fictional violent events depicted in extracts from Homer) was used in a self-contained classroom for nine EBD children with learning disabilities. In dramatic inquiry students and teachers, working collaboratively, engage in extended inquiry into a topic via dialogue and dramatising fictional events; social-emotional learning can occur in tandem with academic learning. Using especially Maslow's theory of hierarchical human needs, the authors analyse for the significance of using dramatic inquiry in the social-emotional learning of the four students: developing a more positive self-concept, social reciprocity, a sense of community cohesion, and some shift in their vision of who they are and might become.